2015
DOI: 10.1038/ncomms8620
|View full text |Cite
|
Sign up to set email alerts
|

PTEN regulates DNA replication progression and stalled fork recovery

Abstract: Faithful DNA replication is a cornerstone of genomic integrity. PTEN plays multiple roles in genome protection and tumor suppression. Here we report on the importance of PTEN in DNA replication. PTEN depletion leads to impairment of replication progression and stalled fork recovery, indicating an elevation of endogenous replication stress. Exogenous replication inhibition aggravates replication-originated DNA lesions without inducing S-phase arrest in cells lacking PTEN, representing replication stress toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 31 publications
3
90
0
Order By: Relevance
“…In addition, deletion of PTEN can initiate a replication stress cascade and thus regulate the cell cycle. 23 PTEN-L is a secretory translational variant. It has an additional 173 aa at the N terminus of PTEN.…”
Section: Pten and Tumor Suppressionmentioning
confidence: 99%
“…In addition, deletion of PTEN can initiate a replication stress cascade and thus regulate the cell cycle. 23 PTEN-L is a secretory translational variant. It has an additional 173 aa at the N terminus of PTEN.…”
Section: Pten and Tumor Suppressionmentioning
confidence: 99%
“…[1][2][3][4] PTEN targets phosphatidylinositol-3,4,5-triphosphate (PIP3) and antagonizes the major survival pathway regulated by phosphatidylinositol 3-kinase (PI3K)/Akt. [5][6][7] Increasing evidence indicates that nuclear PTEN has fundamental functions in maintenance of chromosomal stability, 2,[8][9][10][11][12][13][14] suggesting there are as yet unidentified mechanisms in the process of chromosome inheritance for which the function of PTEN is indispensable. It has been shown that PTEN plays an essential role in maintaining the structural integrity of individual chromosomes, 2 which supports recognition of PTEN as a guardian of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of PTEN expression results in Rad51 dissociation from DNA replication forks, and subsequent destabilization and stalled replication. Cells lacking PTEN have deficient HRR functions, likely due to reduced Rad51 recruitment to the replicating DNA, culminating in loss of fidelity during DNA synthesis (44). As with BRCA1/2 mutations, cells lacking PTEN function are prone to HRR deficiencies and, subsequently, have been shown to be sensitive to PARPi (45,46).…”
Section: Discussionmentioning
confidence: 99%